Overexpression of MYCT1 Inhibits Proliferation and Induces Apoptosis in Human Acute Myeloid Leukemia HL-60 and KG-1a Cells in vitro and in vivo - Fu, Shuang; Fu, Yu; Chen, Fang; Hu, Yanping; Quan, Bi; Zhang, Jihong (Frontiers in Pharmacology, 2018)
MYC target 1 (MYCT1), a direct target gene of c-Myc, is a novel candidate tumor suppressor gene first cloned from laryngeal squamous cell carcinoma. The downregulation of MYCT1 has been reported to be associated with carcinogenesis. However, the role of MYCT1 in the development and progress of Acute myeloid leukemia (AML) remains unknown and requires further investigation. In this study, we first found that the expression level of MYCT1 was significantly lower in the bone marrow derived from AML patients than that from healthy individuals. The low expression of MYCT1 in AML bone marrow may be due to the hypermethylation in its promoter. MYCT1 expression was strongly associated with French-American-British classifications of AML. The low expression level of MYCT1 was more often observed in patients of M1, M5 and M6 types. In vitro, lentiviral particles carrying the complete CDS of MYCT1 gene were used to mediate the forced overexpression of MYCT1 in two AML cell lines, HL-60 and KG-1a. MYCT1 overexpression significantly inhibited cell proliferation, arrested cell cycle at G0/G1 phase, and downregulated the expression of cyclins D and E. Moreover, MYCT1 overexpression triggered apoptosis in AML cells, which was accompanied by enhanced cleavage of caspase-3 and caspase-9, upregulated expression of B-cell lymphoma 2 (Bcl-2)-associated X protein (Bax), and downregulated Bcl-2. Finally, in BALB/c-nu nude mice bearing xenograft tumors generated by HL-60 and KG-1a cells, we noted that the intratumoral injection of MYCT1 lentivirus repressed tumor growth and led to massive apoptosis. In summary, our results reveal that MYCT1's promoter is hypermethylated and its expression is downregulated in the bone marrow of AML patients. MYCT1 plays a tumor-suppressive role, and it may serve as a promising target for the genetic therapeutic strategy in treating AML.